Cloud Based Secure Deduplication of Textual Data Using AES and Deduct Mechanism - M. Sivasankar Naik; Dr. K. Venkataramana (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In the digital age, managing the exponential growth of textual data while ensuring security in cloud environments is a significant challenge. DEDUCT introduces a secure data deduplication system utilizing Advanced Encryption Standard (AES) for both encryption and decryption processes, aimed at enhancing storage efficiency and data security. By leveraging AES, the system ensures that textual data stored in the cloud remains confidential and protected from unauthorized access. The proposed framework delineates specific roles for cloud administrators, users, owners, and potential attackers, each with clearly defined functionalities. For instance, owners can securely upload and manage files, authorize user access, and perform file audits, while users can request access to these files under stringent security protocols. The SQL database supports these operations, maintaining the integrity and availability of the data. Studies indicate that data deduplication can reduce storage needs by 90-95%, highlighting the effectiveness of such systems in managing large-scale data efficiently while ensuring robust security measures (Kwon et al., 2020; Hur et al., 2016). This approach not only enhances storage efficiency but also significantly mitigates the risks associated with data breaches, making DEDUCT a vital solution for secure cloud storage environments.